USM SCIENTIST SPEARHEADS BIODIVERSITY CONSERVATION WORK IN MYANMAR AND ASEAN - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 19 December 2016 – Universiti Sains Malaysia (USM) scientist Professor Dr. Mashhor Mansor was recently invited as a keynote speaker at the first international workshop on biodiversity focusing on Myanmar flora and fauna in University of Yangon, Myanmar in conjunction with its 96 anniversary since its establishment in 1920.